(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In the article, the concept of administrative procedures, the issues of improving the Law of the Republic of Uzbekistan "On Administrative Procedures" based on the experience of foreign countries, changing the concept of “administrative document” to “administrative act”, existing legislation in changing, canceling or invalidating an administrative document problems and their solutions were revealed. The implementation of these suggestions will help to eliminate legal gaps in the legislation and to establish uniform legal mechanisms, to make fair administrative decisions, to prevent unnecessary spending of time and money by citizens, and to save state resources.